Fuzzy model and method for farmland fertilization planning - Vergara Moreno, Edmundo Ruben (2021)
Fuzzy set theory was used for modeling and fuzzy optimization methods for solving the problem of farmland fertilization considering the fuzzy constraints and costs. A method solution was proposed based on the proposals of Lai-Hwang, Leberling and Verdegay. The methodology that transforms a fuzzy objective into a multi-objective optimization problem, and these into fuzzy goals, and finally alfa-cut is used to transform it into a classic problem. The method is illustrated with an example. The solution obtained is a triple that represents a fuzzy number, which provides greater flexibility to the decision maker.